2012
DOI: 10.5897/ijmms12.009
|View full text |Cite
|
Sign up to set email alerts
|

Chronic care model for diabetics by pharmacist home health in Bangkok Metropolitan: A community based study

Abstract: Diabetes was increased in Thailand with increasing burden of morbidity and mortality. There were 42.8% of diabetes patients in Bangkok who had been treated, but the disease conditions were uncontrolled. Diabetes with drug related problems (DRPs) frequently occurred, leading to problems of uncontrolled disease conditions. The objective of this study was to apply chronic care model (CCM) which has been introduced using medication therapy management (MTM) services by community pharmacist home health care and moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 13 publications
1
12
0
1
Order By: Relevance
“…When assessing the quality of the evidence by peer‐review following the criteria in Table , 18 studies were acceptable and eligible for analysis (Figure ). Of the 18 articles, one article provided more than one outcome; thus, the total number of papers when grouping by outcomes was 20 . Ten studies were excluded due to a high dropout rate and/or small sample size, as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When assessing the quality of the evidence by peer‐review following the criteria in Table , 18 studies were acceptable and eligible for analysis (Figure ). Of the 18 articles, one article provided more than one outcome; thus, the total number of papers when grouping by outcomes was 20 . Ten studies were excluded due to a high dropout rate and/or small sample size, as shown in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 included studies, there were 10 clinical outcome studies, two qualitative studies, three survey studies, and three economic studies that met all of the quality assessment criteria. Three studies were randomized controlled trials, three studies were clinical trials with a control group, and four were clinical trials without a control group . For the economic study, there was no analysis for the incremental costs and effects of each strategy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations